(untitled) (Web of Teachers: Inderscience Research, 2025)
The automotive industry is one of the key sectors of the economy of Uzbekistan. From 2022 to 2024, this industry has undergone significant changes associated with the introduction of innovative technologies, the development of new models and an export orientation. This article discusses the main trends that determined the development of the automotive industry in Uzbekistan during this period.